Doctoral dissertation: The socio-economic impacts of urban regeneration programs as a tool of housing in post-socialist era: a comparison of Hungarian case studies - Ntombifuthi Precious Nzimande (Boletín de la Asociación de Geógrafos Españoles)
Nzimande, Ntombifuthi Precious. The socio-economic impacts of urban regeneration programs as a tool of housing in post-socialist era: a comparison of Hungarian case studies. University of Szeged (Hungary), November 2022. Directors: Prof. Tivadar Tóth, Dr. György Csomós, Dr. Erika Nagy, Dr. Márton Berki & Dr. Márton Kiss.